Comparison of Peak Oxygen Consumption During Exercise Testing Between Sexes Among Children and Adolescents in Taiwan - Tuan, Sheng-Hui; Chen, Guan-Bo; Chen, Chia-Hsin; Chen, Yi-Jen; Liou, I-Hsiu; Su, Yen-Tung; Lin, Ko-Long (Frontiers in Pediatrics, 2021)
Objective: Studies among Western children have observed that the peak oxygen consumption (peak VO2) of boys is higher than that of girls, and this difference increases as children progress through adolescence. However, the maturation process and social expectation toward Eastern boys and girls are much different from their Western counterparts. This study aimed to provide baseline information on cardiopulmonary fitness (CRF) of Taiwanese children and adolescents in relation to age and sex. We also evaluated the correlation between body mass and CRF and compared the CRF between non-obese and overweight/obese children. Methods: We conducted a retrospective study of children and adolescents aged 4–18 years in Taiwan. Participants were classified into four groups based on age (group 1, aged 4–6; group 2, aged 7–9; group 3, aged 10–13; and group 4, aged 14–18 years). All participants completed symptom-limited exercise test by treadmill and anthropometric measurements through bioelectrical impedance method. Results: In total, 897 (448 men, 449 women) participants were analyzed. Boys had higher peak VO2 (all p<0.01) and peak metabolic equivalent (MET, all p<0.05) than girls in all the four groups. Age signiﬁcantly (P < 0.001) correlated with peak VO2 in all participants, boys, and girls, with coefficients of determination (R2) of 0.9349, 0.9433, and 0.9085, respectively. The peak VO2 (all p<0.001) of all the groups and peak MET (all p<0.05) of group 2-4 associated with BMI and FMI modestly to moderately. Non-obese children had higher peak MET in group 1 (p=0.049) and group 2-4 (all p<0.001) than overweight/obese children significantly. Conclusions: The difference in peak VO2 and anthropometry–body composition between sexes was observed earlier in children in Taiwan than those in Western countries. Non-obese children had better CRF than overweight/obese children and the difference presented since preschool age.